Hydromorphodynamics Simulation for Selected Stretch of Euphrates River within Al-Anbar Governorate (Journal of Engineering, 2023)
In this study, the hydromorphodynamic simulation of a stretch of the Euphrates River was conducted. The stretch of the Euphrates River extended from Haditha dam to the city of Heet in Al-Anbar Governorate and it is estimated to be 124.4 km. Samples were taken from 3 sites along the banks of the river stretch using sampling equipment. The samples were taken to the laboratory for grain size analysis where the median size (D50) and sediment load were determined. The hydromorphodynamic simulation was conducted using the NACY 2DH solver of the iRIC model.  The model was calibration using the Manning roughness,    sediment load, and median particle size and the validation process showed that the error between the simulation and the recorded data was minimum. After calibration, three different scenarios were considered and the scenarios were based on different river discharges (low, average, and flood discharge).  Four statistical indices were used to check the predicted values of the velocities and water depth in various sections of the Euphrates River section at the city of Heet and these indices were Mean Absolute Deviation (MAD), Mean Square Error (MSE), Root MSE (RMSE), and the Mean Absolute Percentage Error (MAPE). For velocity, values of the above indices for the first scenario were found to be 0.19, 0.046, 0.21, and 0.17 respectively. However, for water depth, values for the above statistical indices were found to be 0.07, 0.01, 0.01, and 0.13 respectively. The values confirmed the accuracy of the prediction of model iRIC Nacy2DH.